Neuroprotective effect of deferoxamine on erastininduced ferroptosis in primary cortical neurons - Zhang, Yan; Fan, Bao-You; Pang, Yi-Lin; Shen, Wen-Yuan; Wang, Xu; Zhao, Chen-Xi; Li, Wen-Xiang; Liu, Chang; Kong, Xiao-Hong; Ning, Guang-Zhi; Feng, Shi-Qing; Yao, Xue (Neural regeneration research, 2020)
The iron chelator deferoxamine has been shown to inhibit ferroptosis in spinal cord injury. However, it is unclear whether deferoxamine directly protects neurons from ferroptotic cell death. By comparing the survival rate and morphology of primary neurons and SH-SY5Y cells exposed to erastin, it was found that these cell types respond differentially to the duration and concentration of erastin treatment. Therefore, we studied the mechanisms of ferroptosis using primary cortical neurons from E16 mouse embryos. After treatment with 50 μM erastin for 48 hours, reactive oxygen species levels increased, and the expression of the cystine/glutamate antiporter system light chain and glutathione peroxidase 4 decreased. Pretreatment with deferoxamine for 12 hours inhibited these changes, reduced cell death, and ameliorated cellular morphology. Pretreatment with the apoptosis inhibitor Z-DEVD-FMK or the necroptosis inhibitor necrostain-1 for 12 hours did not protect against erastin-induced ferroptosis. Only deferoxamine protected the primary cortical neurons from ferroptosis induced by erastin, confirming the specificity of the in vitro ferroptosis model. This study was approved by the Animal Ethics Committee at the Institute of Radiation Medicine of the Chinese Academy of Medical Sciences, China (approval No. DWLL-20180913) on September 13, 2018.